Report on the practice in industry in fish preservation. - Cano, Teresita B. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1965)
In other parts of the world where populations suffer from the effects of a serious shortage of protein, vast fish resources are known to exist. Yet in such localities, those resources have remained virtually untapped because facilities for the preservation, shortage and distribution are lacking. It is customary for us to refer to the national diet as rice and fish. It is no because these are the only items of food but it is because of its most important components. Rice seems to be the arbiter of prices of most commodities in the Philippines. A change in the price of a ganta of rice may change the prices of many other commodities. But what is the place of fish in our daily life? Its role is not as colorful as that of rice. The disappearance of rice in the market stalls is at once followed by near panic. But when fish is not found in the fish stalls, nothing happens. No news and complaints about it reach the newspaper headlines. It is because we are accustomed to reckon starvation on the basis of rice alone. But rice represents only the carbohydrate part of our diet. When we do not have enough rice, we starve only from lack of fish just as badly as we starve from lack of rice. In order that locally existing marine products can be made available as food, it has been contemplated to prepare from fish stable products of high nutritional value that can be stored and transported as used as a valuable supplement to local diets. In this case, the people of the world can produce enough food to make the world get rid of hunger if they use the best methods of food production.
Report (Undergraduate. Fish Preservation) College of Fisheries, University of the philippines, 1965.1956.
Keywords: Fish-Preservation.